Autism spectrum disorder assessment in schools - Dilly, Laura J.; Hall, Christine M. (Routledge, 2019)
Autism Spectrum Disorder Assessment in Schools serves as a guide on how to assess children for autism spectrum disorders (ASD), specifically in school settings. Dilly and Hall offer a general overview of ASD, describe ASD assessment best practices, and explain the process of identifying ASD in schools. Current research and up-to-date science is incorporated in a practitioner-friendly manner, and short case vignettes will increase the accessibility of the book content and illustrate principles. As the rates of ASD reach 1/59 children, and school psychologists are increasingly expected to possess expertise in the assessment of ASD, this book serves as a must have for school psychologists, school social workers, and other practitioners. -- Provided by publisher
Description based on print version record
Keywords: Autism spectrum disorders in children / Education; Autistic children / Services for; Autism spectrum disorders in children